Oral cancer in Scotland: changing incidence and mortality. Issue 6862 (7th November 1992) - Macfarlane, G. J.; Boyle, P.; Scully, C.
Abstract : OBJECTIVES–To determine the incidence of oral cancer in Scotland between 1960 and 1989 and oral cancer mortality from 1911 to 1989. SETTING–Data were obtained on oral cancer incidence from the information and statistics division of the Common Services Agency of the Scottish Health Service and mortality data from the office of the registrar general for Scotland. RESULTS–Mortality from intraoral cancers in Scotland substantially declined throughout this century until the mid-1970s. This trend, however, was then reversed, and fourfold increases in incidence were observed in younger age groups after 1960. Death rates in these younger age groups increased to levels previously recorded in the 1940s. These increases seemed to be cohort based and may therefore continue into the future. CONCLUSIONS–Reasons for increasing rates among younger age groups are speculative and rely on combining knowledge about risk factors and available ecological data. Though increases in incidence at younger ages do not result in a large change in the number of cases diagnosed, possible similar increases continuing into older ages, when oral cancer is more common, will correspond to a much larger increase in the actual number of cases. Given that such a large attributable risk is associated with tobacco and alcohol, however, these increases may be preventable.